Crafting Employee Engagement in Public Sector Delayering: From Transparency, Leadership to Trust - Khurohman, Akhmad Heni; Desiana, Putri Mega (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study is based on the understanding that organizational changes, such as delayering, can influence the level of employee engagement. Previous studies have acknowledged the roles of transparent communication, transformational leadership, and employee organizational trust in enhancing the level of employee engagement. The aim of this study is to analyze the influence of transparent communication and transformational leadership on employee engagement through the mediation of employee organizational trust in the context of organizational change. This study adopts a cross-sectional design with purposive sampling technique. The respondents are the Firstluo-Level Functional PD appointed through the delayering mechanism in the Indonesian Douane Authority. A total of 424 respondent data were collected and further analyzed. Hypothesis testing was conducted using Structural Equation Model with Lisrel 8.8. The results show that transparent communication and transformational leadership have a significant positive effect on employee engagement. Furthermore, employee organizational trust partially mediates the relationship between transparent communication and transformational leadership with employee engagement. This study provides valuable insights for human resource management practitioners, emphasizing the importance of fostering transparent communication, implementing transformational leadership practices, and nurturing organizational trust to effectively enhance employee engagement during organizational change, particularly in the context of delayering within public sector organizations.